Case study как современный метод изучения ситуаций по предмету «Современный литературный русский язык. Лексика» - Григорьева, М (FAN va JAMIYAT, 2025)
The article examines the use of the Case Study method as a modern and effective approach to studying situations in the subject "Modern Literary Russian Language. Lexicon." The theoretical foundations of this method, its advantages in the context of teaching vocabulary, as well as the features of its implementation in the educational process, are considered.